2023
DOI: 10.3389/fgene.2022.989199
|View full text |Cite
|
Sign up to set email alerts
|

RNA Pol III promoters—key players in precisely targeted plant genome editing

Abstract: The clustered regularly interspaced short palindrome repeat (CRISPR)/CRISPR-associated protein Cas) system is a powerful and highly precise gene-editing tool in basic and applied research for crop improvement programs. CRISPR/Cas tool is being extensively used in plants to improve crop yield, quality, and nutritional value and make them tolerant to environmental stresses. CRISPR/Cas system consists of a Cas protein with DNA endonuclease activity and one CRISPR RNA transcript that is processed to form one or se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 113 publications
(158 reference statements)
0
13
0
Order By: Relevance
“…The core competent for CRISPR/Cas9 system contains the expression cassettes of sgRNA and the SpCas9 nuclease. Guide RNAs for genome editing have been produced using a range of Pol III promoters (Xie et al, 2015; Kor et al, 2022). We found seven U6 small nuclear ribonucleoprotein genes ( Ceric.17G074700, Ceric.33G040100, Ceric.09G088700, Ceric.02G026900, Ceric.1Z290000, Ceric.03G070800, Ceric.03G071600 ) in the C. richardii genome (https://phytozome-next.jgi.doe.gov/info/Crichardii_v2_1), which showed high expression in gametophyte, leaf, stem, and root (Supplemental Figure S1A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The core competent for CRISPR/Cas9 system contains the expression cassettes of sgRNA and the SpCas9 nuclease. Guide RNAs for genome editing have been produced using a range of Pol III promoters (Xie et al, 2015; Kor et al, 2022). We found seven U6 small nuclear ribonucleoprotein genes ( Ceric.17G074700, Ceric.33G040100, Ceric.09G088700, Ceric.02G026900, Ceric.1Z290000, Ceric.03G070800, Ceric.03G071600 ) in the C. richardii genome (https://phytozome-next.jgi.doe.gov/info/Crichardii_v2_1), which showed high expression in gametophyte, leaf, stem, and root (Supplemental Figure S1A).…”
Section: Resultsmentioning
confidence: 99%
“…We found seven U6 small nuclear ribonucleoprotein genes ( Ceric.17G074700, Ceric.33G040100, Ceric.09G088700, Ceric.02G026900, Ceric.1Z290000, Ceric.03G070800, Ceric.03G071600 ) in the C. richardii genome (https://phytozome-next.jgi.doe.gov/info/Crichardii_v2_1), which showed high expression in gametophyte, leaf, stem, and root (Supplemental Figure S1A). However, the promoters of these C. richardii genes do not contain the upstream sequence element (USE) and TATA elements, which are the typical structural properties of the Pol III promoters (Kor et al, 2022). Therefore, we used the sequences of the A. thaliana U6-26 snRNA (X52528, AT3G13857) and the T. aestivum U6 gene (X52528, ENSRNA050022746-T1) (Poovaiah et al, 2021) sequences to compare with the upstream U6 promoter regions in C. richardii .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Cas9 expression in germ cells (oocytes, daughter cells, and early embryos) leads to heritable editing and reduces somatic mutations in organogenic plants. Efficient CRISPR/Cas9 systems based on germline-specific promoters may reduce chimerism and thus reduce the workload for the characterization of edited plants [ 170 , 171 , 172 ].…”
Section: Strategies and Methods For Optimizing Crispr/cas9 Gene-editi...mentioning
confidence: 99%
“…Additionally, RNA transcribed by Pol III promoters is usually not capped or polyadenylated, allowing the transcription product to function immediately in the cell. 21 , 22 The U6 promoter uses G as the transcription initiation site. Many studies have shown that the efficiency of a U6 promoter is substantially degraded when used in a distantly related species.…”
Section: Introductionmentioning
confidence: 99%